2020
DOI: 10.1177/2050157920927451
|View full text |Cite
|
Sign up to set email alerts
|

Mobile communicating place and place-inscribed communicative mobilities: Shaping alternative consumer cultures in mobile media communication

Abstract: This study aims to update notions of how the practical elements of mobile communication (i.e., microcoordination and synchronization) alter the interconnectedness between places and mobilities. Based on ethnographic research on personal shoppers’ mobile purchasing practices between mainland China and Hong Kong (HK), this article argues that mobile communication, as a social practice, extends relational places in cross-border shopping, on the one hand, and transforms the performances of mobilities that are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Smartphone and mobile social media use seems to reinvigorate the multiple forms of different inclusion and exclusion, as it blurs the boundaries of “us” and “them” and promises to blur online/offline boundaries of social interactions (Bolander & Locher, 2020; Lim & Pham, 2016; Stewart & Gachago, 2016). However, even if with the aid of mobile social media (Wei et al, 2018; Xie, 2021), the borders as “complex social institutions” are never being crossed and lead only to digital and social inclusion (Mezzadra & Neilson, 2013, p. 3). Internal borders, such as social and cultural boundaries, will be never-ending but “even a lifetime offers insufficient time to complete” (Hurd et al, 2017, p. 13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smartphone and mobile social media use seems to reinvigorate the multiple forms of different inclusion and exclusion, as it blurs the boundaries of “us” and “them” and promises to blur online/offline boundaries of social interactions (Bolander & Locher, 2020; Lim & Pham, 2016; Stewart & Gachago, 2016). However, even if with the aid of mobile social media (Wei et al, 2018; Xie, 2021), the borders as “complex social institutions” are never being crossed and lead only to digital and social inclusion (Mezzadra & Neilson, 2013, p. 3). Internal borders, such as social and cultural boundaries, will be never-ending but “even a lifetime offers insufficient time to complete” (Hurd et al, 2017, p. 13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on mobile media and migration has captured the affordances of smartphones, mobile technologies, and mobile social media that provide migrants with homogenous space-time mobilities (e.g., Georgiou & Leurs, 2022; Järv et al, 2022; Xie, 2021), but little attention has been paid to the complicated spatial-temporal mobility landscape (re)constituted by mobile social media. On the one hand, mobile use of social media supplements migrants’ physical mobility based on its portability, locatability, and multimediality (Ling & Campbell, 2009; Marvin, 2013; Schrock, 2015), as smartphones are easy to carry and allow migrants to “virtually engage with physical environments through GPS tracking and can be used synchronously with other activities and applications” (Kuru et al, 2017, p. 104).…”
Section: Spatial-temporal Mobility In Mobile Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Media and communication studies have demonstrated remarkable agility for methodological innovation in the past, not least because the inflexibility of institutionalization into competing camps is less pronounced here than elsewhere in the social sciences (Helles Achmad Maulana Sirojjudin: Utilization of Big Data Analysis Through Public Video, Virus Data Cooperation, and Social Media as the Surveillance to COVID-19 in Indonesia & Ørmen, 2020;Xie, 2021). Recognizing the potential of Big Data to support many kinds of explanations, perhaps it could repeat that success.…”
Section: Discussionmentioning
confidence: 99%
“…However, it would not be quite right to consider the images of death and danger that arise in the Internet space only from the point of view of their digital nature, since most of them, united by the general term "creepypasta", show similar signs with folklore narratives and myths. The peculiarity of broadcasting images of waiting for death and danger in the Internet space (Xie, 2020) is the inability to maintain linear subject-object relations with this image. "Creepypasta", as a special kind of narrative and a set of "terrible images and codes" in the Internet space, has a kind of compulsive force that forces a person to lose the usual position of the subject, depriving him of the ability to identify narratives and other people as objects.…”
Section: Introductionmentioning
confidence: 99%